VD_FINDINFO HC / 2025 / 265 vom 3. Februar 2025 - VD Tribunal cantonal (2025)
ARBITRAGE, SPORT, RÉVISIONDÉCISION, FOOTBALL, TRIBUNAL ARBITRAL DU SPORT, JUGE ARBITRE | 356 al. 1 let. a CPC (CH), 367 CPC (CH), 396 CPC (CH), 397 al. 1 CPC (CH)